2018
DOI: 10.1103/physrevapplied.9.034010
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transport Properties of Carbon-Nanotube Networks: The Effect of Nitrate Doping on Intratube and Intertube Conductances

Abstract: The conductivity of carbon-nanotube (CNT) networks can be improved markedly by doping with nitric acid. In the present work, CNTs and junctions of CNTs functionalized with NO 3 molecules are investigated to understand the microscopic mechanism of nitric acid doping. According to our density-functional-theory band-structure calculations, there is charge transfer from the CNT to adsorbed molecules indicating p-type doping. The average doping efficiency of the NO 3 molecules is higher if the NO 3 molecules form c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The local conductivity minima occur when the bands are flat such as at −0.5 and −1.5 eV. These are Van Hove singularities, which have local maxima in the density of states and have previously been noted for CNT systems …”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The local conductivity minima occur when the bands are flat such as at −0.5 and −1.5 eV. These are Van Hove singularities, which have local maxima in the density of states and have previously been noted for CNT systems …”
Section: Resultsmentioning
confidence: 58%
“…However, standard percolation theory lacks the electronic structure information of the nanotubes. Computational studies based on density-functional theory (DFT) have revealed how the overall conductivity and electronic structure of a CNT network are changed by analytes or dopants such as H 2 , nitrogen oxides, , gold chlorides, , halogens, and transition metals . DFT methods predict significant variation in the electronic transport and reactivity of different configurations of N-substituted nanotubes. Enhanced conductivity and improved sheet resistance have been measured experimentally in films containing Cl anions or doped with Cr .…”
Section: Introductionmentioning
confidence: 99%
“…In one of our studies, it was observed that the complexes of indigo wrapped over CNT exhibit p‐type charge transfer characteristics . Very recently, Ketolainen et al examined the adsorption of nitrates on the surface of CNT and found a p‐type characteristics owing to the charge transfer from donor CNT to acceptor nitrates . On the other hand, Koizhaiganova and coworkers reported n‐type charge‐transfer characteristics for the complexes of CNT with aromatic amines wherein CNT acts as an acceptor for the donor amines .…”
Section: Introductionmentioning
confidence: 59%
“…Intense Raman peaks have been observed from nanotubes with encapsulated S . The adsorption of H 2 was more favorable on transition-metal-decorated CNTs than pristine CNTs. NO 3 , AuCl 3 , AuCl 4 , or halogens induce p-type behavior in semiconducting CNT networks. Atomic gold clusters at the CNT intersection increase the electrical conductivity if the clusters have an odd number of atoms …”
Section: Introductionmentioning
confidence: 99%